Elucidation of plasma protein binding, blood partitioning, permeability, CYP phenotyping and CYP inhibition studies of Withanone using validated UPLC method: An active constituent of neuroprotective herb Ashwagandha. (24th April 2021) - Singh, Sandeep K.; Valicherla, Guru R.; Bikkasani, Anil K.; Cheruvu, Srikanth H.; Hossain, Zakir; Taneja, Isha; Ahmad, Hafsa; Raju, Kanumuri S.R.; Sangwan, Neelam S.; Singh, Shio K.; Dwivedi, Anil K.; Wahajuddin, Mohammad; et al.
Abstract: Ethnopharmacological relevance: Withanone (WN), an active constituent of Withania somnifera commonly called Ashwagandha has remarkable pharmacological responses along with neurological activities. However, for a better understanding of the pharmacokinetic and pharmacodynamic behavior of WN, a comprehensive in-vitro ADME (absorption, distribution, metabolism, and excretion) studies are necessary. Aim of the study: A precise, accurate, and sensitive reverse-phase ultra-performance liquid chromatographic method of WN was developed and validated in rat plasma for the first time. The developed method was successfully applied to the in-vitro ADME investigation of WN. Material and methods: The passive permeability of WN was assayed using PAMPA plates and the plasma protein binding (PPB) was performed using the equilibrium dialysis method. Pooled liver microsomes of rat (RLM) and human (HLM) were used for the microsomal stability, CYP phenotyping, and inhibition studies. CYP phenotyping was evaluated using the specific inhibitors. CYP inhibition study was performed using specific probe substrates along with WN or specific inhibitors. Results: WN was found to be stable in the simulated gastric and intestinal environment and has a high passive permeability at pH 4.0 and 7.0 in PAMPA assay. The PPB of WN at 5 and 20 μg/mL concentrations were found to be high i.e. 82.01 ± 1.44 and 88.02 ± 1.15%, respectively. The in vitro half-life of WN in RLM and HLM was found to be 59.63 ± 2.50 and 68.42 ± 2.19 min, respectively. CYP phenotyping results showed that WN was extensively metabolized by CYP 3A4 and1A2 enzymes in RLM and HLM. However, the results of CYP Inhibition studies showed that none of the CYP isoenzymes were potentially inhibited by WN in RLM and HLM. Conclusion: The in vitro results of pH-dependent stability, plasma stability, permeability, PPB, blood partitioning, microsomal stability, CYP phenotyping, and CYP inhibition studies demonstrated that WN could be a better phytochemical for neurological disorders. Graphical abstract: Image 1